2020
DOI: 10.1101/2020.06.08.20120584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 virus and antibodies in front-line Health Care Workers in an acute hospital in London: preliminary results from a longitudinal study

Abstract: Background SARS-CoV-2 infection in Healthcare Workers (HCWs) is a public health concern during the pandemic. Little description has been made of their antibody response over time in the presence or absence detectable SARS-CoV-2 RNA and of symptoms. We followed a cohort of patient-facing HCWs at an acute hospital in London to measure seroconversion and RNA detection at the peak of the pandemic in London. Methods We enrolled 200 front-line HCWs between 26 March and 8 April 2020 and collected twice-weekly self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 19 publications
5
64
2
1
Order By: Relevance
“…The levels of seroprevalence for CLA IgG (2.28%) at the beginning of the study and of seroconversion to this antibody (5.98%) are comparable to those reported in other studies and, overall, higher than those observed in the general population [1][2][3][4][5][6]. In a comparable study in England that followed 200 front line HCW for two weeks, they found that 20% of them seroconverted during the study, but 25% were already seropositive at the beginning of the study [1]. Most likely, the higher numbers in the English study compared with our study are due to the differences in the populations studied (front line workers vs a mixed population of medical doctors).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The levels of seroprevalence for CLA IgG (2.28%) at the beginning of the study and of seroconversion to this antibody (5.98%) are comparable to those reported in other studies and, overall, higher than those observed in the general population [1][2][3][4][5][6]. In a comparable study in England that followed 200 front line HCW for two weeks, they found that 20% of them seroconverted during the study, but 25% were already seropositive at the beginning of the study [1]. Most likely, the higher numbers in the English study compared with our study are due to the differences in the populations studied (front line workers vs a mixed population of medical doctors).…”
Section: Discussionsupporting
confidence: 86%
“…During the SARS-CoV-2 pandemic healthcare workers (HCW) have been shown to have an increased risk of infection [1][2][3][4][5][6]. Studies in this population in many parts of the world have shown seroprevalences of between 2.4% and 45%, and in general above that of the general population and varing according to multiple factors [1][2][3][4][5][6]. In asymptomatic HCW, at the peak of the pandemic in England, a global seroprevalence rate of 24.4% was found [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study we collected information on 1,038 cases identified in Hong Kong up to 28 April. The majority (51.3%, 533/1,038) of SARS-CoV-2 infections confirmed during the study period (23)(24)(25)(26)(27)(28) were associated with at least 1 of 137 clusters. Cases were linked to clusters (≥2 confirmed cases) based on the reported contact histories between cases (Methods).…”
Section: Sars-cov-2 Cases Confirmed Between 23 January and 28mentioning
confidence: 96%
“…Despite implementation of WHO guidance designed to reduce in-hospital spread, 1 nosocomial and HCW infection have remained prominent features of the current COVID-19 pandemic, with 43.5% of UK HCWs becoming seropositive over a 1-month period in one recent study. 2 Better understanding of in-hospital infection sources is therefore urgently needed. Pleural procedures are not currently considered aerosol-generating by the WHO, 1 and special precautions to mitigate against viral transmission and/or to protect HCWs are not currently recommended.…”
Section: Introductionmentioning
confidence: 99%